2015
DOI: 10.1073/pnas.1421020112
|View full text |Cite
|
Sign up to set email alerts
|

Plant nanobionic materials with a giant temperature response mediated by pectin-Ca 2+

Abstract: Conventional approaches to create biomaterials rely on reverse engineering of biological structures, on biomimicking, and on bioinspiration. Plant nanobionics is a recent approach to engineer new materials combining plant organelles with synthetic nanoparticles to enhance, for example, photosynthesis. Biological structures often outperform man-made materials. For example, higher plants sense temperature changes with high responsivity. However, these properties do not persist after cell death. Here, we permanen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…Shown in Fig. 2 c, Giacomo et al [ 76 ] proposed a biomimetic material with excellent temperature response sensitivity made of isolated plant cells and carbon nanotubes (MWCNT) using plant nano-biomimetic technology. Using CNTs as a channel to connect cells directly, creating a bionic material with an effective temperature resistivity (TCR) of , which is two orders of magnitude higher than the current best sensor, and the monitoring temperature range is 35–75 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shown in Fig. 2 c, Giacomo et al [ 76 ] proposed a biomimetic material with excellent temperature response sensitivity made of isolated plant cells and carbon nanotubes (MWCNT) using plant nano-biomimetic technology. Using CNTs as a channel to connect cells directly, creating a bionic material with an effective temperature resistivity (TCR) of , which is two orders of magnitude higher than the current best sensor, and the monitoring temperature range is 35–75 °C.…”
Section: Methodsmentioning
confidence: 99%
“…b The entire surface micrographs of PEO1500/PVDF/Gr [68]. c Schematic diagrams and scanning electron microscopy (SEM) images of cyberwood [76]. d SEM images of the CNT/PEDOT:PSS composite fibers with CNT contents of 40 wt% [75].…”
Section: Thermal Materialsmentioning
confidence: 99%
“…Besides nucleic acids, nanoparticles can also be functionalized with molecules such as fluorescent dyes for intracellular labeling in plants, active molecules for tracking and sensing purposes, and agrochemicals for crop health . Targeted delivery of nanoparticles to certain regions of plant tissue is also important for the creation of biomimetic systems such as light‐harvesting apparatuses, photonic devices, emission sources for near‐infrared communication to electronic devices, and carbon‐negative temperature and environmental sensors . We have previously shown that highly charged nanoceria, a nanoparticle‐based reactive oxygen species (ROS) scavenger, and certain polymer‐wrapped single‐wrapped carbon nanotubes (SWNTs) localized within the chloroplasts when introduced to plant mesophyll tissue, enabling photosynthetic rate augmentation and extending the photoactive lifetime of extracted chloroplasts .…”
Section: Introductionmentioning
confidence: 99%
“…Together with strain and pressure sensors, temperature‐sensitive devices, which can be stretchable and biocompatible at the same time, allow the implementation of noninvasive and unobtrusive systems for health monitoring. As proof of concept, our engineered elastomeric substrate is combined with a layer of pectin, a plant‐derived molecule recently reported to have large temperature–responsivity (see Device Fabrication section). The temperature sensor, consisting of a single pillar (acting as substrate), metal contacts, and the pectin layer (see Figure a), is mounted on a heating/cooling system (see Figure S14, Supporting Information).…”
mentioning
confidence: 99%